Reconstruction of the Assertiveness Scale of Domestic Violence Victims with the Rasch Polytomy Model - Erwinda, Lira; Rohman, Rohman; Fatah, Abdul; Nahwati, Putri (TheraEdu: Journal of Therapy and Educational Psychology, 2025)
The ability to be assertive is an important aspect in the life of every individual, including for women who are victims of domestic violence (DV). Assertiveness reflects a person's ability to convey thoughts, feelings, and needs honestly and firmly without violating the rights of others. In the context of domestic violence, this ability is often hampered by trauma, emotional dependence, and social pressure. This study aims to explore and describe forms of assertive behavior in women who are victims of domestic violence and to assess the quality of the measurement instruments used. This study involved 64 female respondents who experienced domestic violence, using an assertiveness scale specifically designed to understand psychological dynamics in the context of domestic violence. Data analysis was carried out using the Rasch polytomy model approach with the help of WINSTEPS software version 5.50. The results of the study showed that the instrument used had good validity in identifying various levels of assertiveness, ranging from very low to very high. These findings provide important insights for practitioners, such as counselors, psychologists, and social workers, to set service priorities and design more effective intervention approaches. This study also reinforces the importance of a psychometric approach in developing instruments that are sensitive to the context of gender-based violence.